The business cycle in the post-war world: proceedings of a conference held by the International Economic Association - International Economic Association. [from old catalog]; Lundberg, Erik (London, Macmillan, 1955)
Papers presented at the Oxford conference in September 1952 on business cycle research
obn 24/01/2019
Loans
Keywords: Business cycles